EDUCATIONAL TECHNOLOGIES IN PANDEMIC TIMES: EXPERIENCE REPORT: EDUCATIONAL TECHNOLOGIES IN PANDEMIC TIMES: EXPERIENCE REPORT - Feitosa, Ankilma do Nascimento Andrade; Nascimento, Ingridy Michely Gadelha do; Alencar Neta, Raimunda Leite de; Alencar, Matheus Tavares; Tavares, Mariana Machado Leite; Assis, Elisangela Vilar de (Brazilian Journal of Production Engineering, 2020)
The outbreak of the SARS-CoV-2 virus that caused the COVID-19 pandemic put all countries in the world in an emergency and alert situation, implementing control measures, such as social isolation and unit closures, with the school environment being a space for potential transmission risk. Thus, the objective of this work is to report the experience of the members of the Group of Technological Innovations in Higher Education: contemporary challenges of Faculdade Santa Maria, regarding the use of technologies in favor of education during the COVID-19 pandemic. It is a descriptive study, narrative of the type of experience report, carried out in a private college located in the region of the upper sertão of Paraíba. The work arose in order to demonstrate the experience of using technologies in the continuity of the evaluation process of the 2020.1 and 2020.2 academic semester, which began since March 17, where all the institution’s on-site activities were suspended, extending until nowadays, as well as the perception of carrying out learning assessments via remote technology. During the implementation of remote education in the institution, the group developed several activities to support teachers and students who did not have mastery of various technological tools. The use of remote classes provided benefits and challenges among the academic population, since this tool was the only way to continue the school term, however difficulties such as not having access to the internet, difficulty concentrating during classes, among other aspects.